Análise da adaptação familiar e estratégias estabelecidas para construção de vínculos afetivos na adoção tardia - Dugnani, Katia Cristina Bandeira (2009)
Analyzing the risk factors to the infantile development in light of the reality of a country limited in economic resources as Brazil, the observation of abandonment cases of less favored children has become common. In the scope of the parental affective interactions and reduction of the risks for a healthful development, the reconstruction of these affective bonds for innumerable children around the country occurs through the adoption. Specialized literature shows that the late adoption (children above 2 years old) is the most difficult action to be materialized because of the absence of their parents and the lack of care for their real needs. In this way, the objective of this study was to identify to the difficulties and easinesses of the parents in the construction process of affective bonds by pointing out the strategies used in the late adoption considering their expectations and motivations. As a technical resource, it was used an instrument (form), composed of open and closed questions, aiming to characterize the participants. After its gauging (through the semantics and content analysis and application for suitability) with 23 collaborators, the instrument became apt for application in a selected sample. The data acquisition was carried out with 19 enrolled parents who accomplished late adoption in the district of São Carlos-SP. For this purpose, they were divided into groups according with the age of the children at the adoption: group G1 (children adopted with 2 years); group G2 (children adopted between 3 and 6 years of age); and group G3 (children adopted between 7 and 10 years of age). The results have evidenced the late adopters profile, which, in their majority, presented a high level of maturity and education. Besides, the late adopters are above of the national average socio-economic level. The main motivation found for the late adoption was the age of the children adopted, being defined as the act of educate and take care of a child. The major fear of the parents is not related with the former history of the children s life, but with their education. Their concerns turned mainly to inadequate behaviors and attitudes in terms of school discipline, which does not differ from the difficulties pointed out by some parents of the biological-adoptive families, when relating to the education of their children. Given these difficulties, the main strategies established by the parents were the promotion and social interaction, incentive and valorization of production and use of physical restrictions. The positive strategies as the manifestation of love and affection in the education and the support of familiar networks were also pointed out. Thus, it is possible to presume that the present investigation will make viable preventive practices and the knowledge acquired will make possible the elaboration of a directive program for the late adoption.